Pengaruh Tekanan Teman Sebaya Terhadap Perilaku Merokok Pada Remaja di SMP Negeri 16 Kupang - Maria Christine Minarti Liwu; Marni Marni; Shela Christine Pello (Pusat riset dan Inovasi Nasional, 2025)
This study aims to determine the effect of peer pressure on smoking behavior among adolescents at SMP Negeri 16 Kupang. The background of this study is based on the phenomenon of increasing smoking behavior among adolescents, which is greatly influenced by the dynamics of social relationships, especially peer groups. Adolescents are at a developmental stage where social acceptance and the need to be part of a group are very important, so they are vulnerable to the influence of the social environment, including peer pressure to try smoking behavior. This study uses a quantitative approach with the product moment correlation analysis method. The study sample consisted of 223 adolescent respondents aged 11–17 years who were selected proportionally from various classes at SMP Negeri 16 Kupang. The research instrument was a questionnaire that had been tested for validity and reliability. The results showed a significant relationship between peer pressure and smoking behavior, with a significance value of p = 0.000 (p < 0.05), which means the hypothesis is accepted. The correlation value (R) of 0.317 indicates a positive relationship between the two variables, although in the moderate category. The coefficient of determination (R Square) of 0.100 indicates that peer pressure influences smoking behavior by 10%, while the remaining 90% is influenced by other factors such as family environment, media influence, self-esteem, and adolescent psychological conditions. The correlation between peer pressure and smoking behavior was mostly moderate. Interestingly, the results also showed that female adolescents in this study were more likely to exhibit high smoking behavior than male adolescents, indicating a shift in social behavior patterns in female adolescents. These findings have important implications for educators, parents, and policymakers in designing more effective smoking prevention programs that take into account social pressure factors and gender differences.